Efisiensi dan Efektivitas Pengelolaan Sampah Organik dengan Komposting Skala Rumah Tangga di Kabupaten Buleleng: Efficiency and Effectiveness of Organic Waste Management with Household Scale Composting in Buleleng Regency - Sagara, Moh Rizal Ngambah; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Media Ilmiah Teknik Lingkungan (MITL), 2024)
This study focuses on the analysis of domestic waste management in Buleleng Regency based on data from the National Waste Management Information System (SIPSN) managed by the Ministry of Environment and Forestry. The background of this study is grounded on the necessity to comprehend the basic characteristics of waste in Buleleng and its challenges and solutions. Employing descriptive analysis and literature study methods, this research successfully maps the composition, quantity, and waste management methods in the regency. Results indicate that the composition of domestic waste is dominated by specific types and, compared to other urban areas in Indonesia, there are distinct characteristics in waste management in Buleleng. A brief conclusion from this study emphasizes the need for a more integrated and sustainable waste management strategy in Buleleng Regency.